Natality Detail File, 2002 (United States) ([Verlag nicht ermittelbar], 2007)
This collection provides information on live births in the United States during calendar year 2002. The natality data in these files are a component of the vital statistics collection effort maintained by the federal government. Part 1, United States File, contains data on births occurring within the United States to United States residents and nonresidents, while Part 2, United States Territories File, contains data on births occurring in the United States territories of Puerto Rico, the Virgin Islands, Guam, American Samoa, and the Northern Mariana Islands. Geographic variables describing residence for births include the state, county, city, county and city population size, metropolitan statistical area (MSA), primary metropolitan statistical area (PMSA), consolidated metropolitian statistical area (CMSA), New England County metropolitan area (NECMA), and metropolitan/nonmetropolitan county. Other variables include place of delivery, person in attendance, live-birth order, and medical and health data such as the number of prenatal visits, tobacco and alcohol use during pregnancy, method of delivery, medical risk factors, and infant health characteristics. Birth and fertility rates and other statistics related to this study can be found in the National Vital Statistics Report in the codebook documentation. Demographic variables include the child's sex, birthweight, and date of birth, the mother and father's age, race, and ethnicity, as well as the mother's place of birth, marital status, education level, and nation of origin.